The link between periodontitis and atherosclerotic cardiovascular disease in non-Hispanic White adults: NHANES 1999 to 2014 - Qingna Song; Hongyan Zhang; Yuan Su; Jukun Song (PLoS ONE, 2025)
Background Limited research exists on the association between periodontitis and Atherosclerotic Cardiovascular Disease (ASCVD) in American adults. Chronic inflammation from periodontitis may elevate ASCVD risk by promoting systemic inflammation and endothelial dysfunction, supporting the plausibility of this relationship. Therefore, we utilized data from the National Health and Nutrition Examination Survey (NHANES) database to investigate this association. Methods We conducted a cross-sectional study using NHANES data from 1999–2004 and 2009–2014, including 5,380 individuals from the United States. Tooth loss and periodontitis were assessed through full-mouth periodontal examinations. The 10-year ASCVD risk was calculated based on the 2013 American College of Cardiology (ACC) and American Heart Association (AHA) recommendations. We employed univariate and multivariable logistic regression models, as well as subgroup and interaction analyses. Results Among participants, 74.96% experienced tooth loss, 15.99% had moderate/severe periodontitis, and the average age was 59.64 years. ASCVD was found to be associated with moderate/severe periodontitis (OR 1.24, 95% CI 1.01–1.52, P= 0.0411) and tooth loss (OR 1.16, 95% CI 1.09–1.39, P= 0.0248) in logistic regression models after full adjustment. Conclusion Our study establishes a significant link between moderate/severe periodontitis and the increased risk of ASCVD over a decade in American adults aged 40–79 years.